Case report of EPPER Syndrome (eosinophilic polymorphic pruritic eruption associated with radiotherapy) in a patient treated against endometrial cancer - Lam Cham Kee, H-X; Charra-Brunaud, C; Cuny, J-F; Reigneau, M; Vogin, G; Peiffert, D (Cancer radiothérapie, 2013)
Acute and mainly late toxicity is a major concern for radiotherapists. Here, we describe a case of a generalized acute eruption due to radiation, having a superficial and deep perivascular lymphocytic infiltrate with numerous eosinophils found in skin biopsy: the EPPER syndrome (eosinophilic polymorphic pruritic eruption associated with radiotherapy). A patient who had endometrial cancer was treated first by surgery, then radiotherapy developed the day following the end of irradiation a generalized erythematous, pruriginous eruption (pelvis, trunk, lower and upper limbs, neck, face, ears). Different tests with a skin biopsy found a superficial and deep perivascular lymphohistiocytic infiltrate with many eosinophils, confirming an EPPER syndrome. The description of the syndrome was first published in 1999 by Rueda et al. (1999) [1]. Later on, there have only been a few case reports on this subject. This syndrome can be encountered in many cancers, but more frequently in cervix and breast carcinomas and can occur up to nine and a half months after radiotherapy. The pathogenic mechanism is unknown. Antihistamines, topical corticosteroids or oral corticosteroids as well as ultraviolet B therapy have been used successfully to treat EPPER syndrome. Some cases of spontaneous resolution are also described. EPPER syndrome is probably largely underestimated due to its polymorphic characteristics, its occurrence sometimes late after radiotherapy. Its knowledge is essential to inform and treat patients correctly.